2022
DOI: 10.1177/22785337211073635
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 Outbreak on the Stock Market: An Evidence from Select Economies

Abstract: COVID-19 quickly spread all over the world and dramatically affected the financial markets in almost everycountry. Its spread created havoc in the market, and investors fearing risk suffereda significant amount of financialloss in a very short time. This article aims to analyze the impact of COVID-19 on stock markets in the top six affected countries based on the total number of cases confirmed. In addition, it also analyzes the stock market volatility caused by the virus and the abnormal returns generated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 22 publications
1
28
0
3
Order By: Relevance
“…For example, once the news of the first COVID case was reported, BOVESPA fell by −7.26% and MEXBOL by −4.59%. By the end of April 2020, the stock markets continued to decline, but the volatility was higher [ 54 ]. Furthermore, news about vaccination is correlated with the stock market, since the MERVAL, BOVESPA, and IPSA increased their volatility.…”
Section: Resultsmentioning
confidence: 99%
“…For example, once the news of the first COVID case was reported, BOVESPA fell by −7.26% and MEXBOL by −4.59%. By the end of April 2020, the stock markets continued to decline, but the volatility was higher [ 54 ]. Furthermore, news about vaccination is correlated with the stock market, since the MERVAL, BOVESPA, and IPSA increased their volatility.…”
Section: Resultsmentioning
confidence: 99%
“…and from the visual orientation we can see the trend in the data Before dealing with the trend we have to deal with seasonality of data but as the data is daily so there is no need to seasonally adjust the data. After that ADF stationarity test was conducted to all variables and showed that data need to be trend adjusted as shown in table (1).…”
Section: Methodsmentioning
confidence: 99%
“…Since then, the disease has spread globally, resulting in the continuing COVID-19 pandemic. Several publications have reported on the influence of covid on stock markets (1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All the studies analyzed the initial effect of the pandemic; the most widely used methodologies include event studies (Ganie et al 2022;He et al 2020;Huo and Qiu 2020;Hung et al 2021;Jabeen et al 2022;Liu et al 2020;Ofori-Boateng et al 2021), panel data regression (Amin et al 2021;Mdaghri et al 2020;Topaloglu et al 2021) and classic regression models (Ahmed 2020;Ahmed et al 2021;Schoenfeld 2020), among others. These studies, especially those conducted in developed economies, reach a similar main conclusion: they confirm the significant negative effect of COVID-19 on the stock market.…”
Section: Literature Reviewmentioning
confidence: 99%